Monitoring Skin Trauma Healing in Mice Using Second-Harmonic Generation Combined with Optical Coherence Tomography - Ning Wang; Huajiang Wei; Ying Jin; Lianzhou Chen; Qilei Zhang; Xiaoyuan Deng (IEEE Photonics Journal)
Convenient methods for rapidly evaluating wound healing could help clinicians to select effective treatment measures for patients within an appropriate time frame. In this study, we explored the use of second-harmonic generation (SHG) combined with optical coherence tomography (OCT) to monitor the healing state of wounds, including the macromorphology and optical signal characteristics of regenerated tissue. Wounds were imaged and monitored using OCT and SHG on healing days 3, 5, 7, 14, 21, and 28. The accumulation and maturation of newly formed collagen during the healing process was detected using SHG in real time. Additionally, changes in the OCT signal and attenuation coefficient in wounds before and after trauma were measured using the single-scattering OCT model. The wound closure percentage, the SHG intensity of collagen, and the attenuation coefficient of the wounds were analyzed using correlation analysis, which produced correlation coefficients of R12 = 0.944, R 22 = 0.9776, and R32 = 0.9354, respectively. In theory, it is feasible to replace the wound closure percentage with the SHG intensity of collagen and the attenuation coefficient to evaluate wound healing. The OCT and SHG combination could be used to diagnose wound healing in real time.